Experiment Centric Teaching for Reconfigurable Processors. (24th January 2011) - Lagadec, Loïc; Picard, Damien; Corre, Youenn; Lucas, Pierre-Yves
Abstract : This paper presents a setup for teaching configware to master students. Our approach focuses on experiment and leaning-by-doing while being supported by research activity. The central project we submit to students addresses building up a simple RISC processor, that supports an extensible instructions set thanks to its reconfigurable functional unit. The originality comes from that the students make use of the Biniou framework. Biniou is a research tool which approach covers tasks ranging from describing the RFU, synthesizing it as VHDL code, and implementing applications over it. Once done, students exhibit a deep understanding of the domain, ensuring the ability to fast adapt to state-of-the-art techniques.